Observations of milk yield, and calf growth and conversion rate, on three types of cattle in Ghana. II. Effects of plane of nutrition - Montsma, G. (1962)
Productive performance of West African Shorthorn (WAS), N'Dama and Sokoto cattle at Nungua Research Station were investigated. Discussions and comparative data on milk yield of cows and birth weight, weight gain and conversion efficiency of calves under different levels of nutrition included.